Sources of Key Evidences for COVID-19 Pandemic - Shankar, Pathiyl; Jha, Nisha (Europasian Journal of Medical Sciences, 2021)
Coronavirus disease -19 (COVID-19) has become a global pandemic and health emergency. Research and studies are ongoing at a rapid pace. It is challenging to keep pace with the published and ongoing research, especially considering the fact that many show conflicting results. Many organizations have produced key evidence sources focusing on scientific studies about the disease. In this article the authors describe certain important evidence sources and highlight their important features. In this article we have described thirteen high-quality evidence sources which will be useful to researchers, policy makers and others make sense of the rapidly emerging evidence related to COVID-19. As the pandemic continues for the second year some sources dependent on volunteers are facing challenges in regularly updating the evidence.